MENUJU MASYARAKAT DESA SADAR HUKUM, MANDIRI, DAN PEDULI LINGKUNGAN DI DESA CIJENGKOL – KABUPATEN BEKASI - Mahardhika Tryatmadja; Markus Frederik Joshua; Rheina Nabilla Putri; Diana Fitriana (Abdi Bhara, 2023)
The drug problem in Indonesia is still something thatis urgent and complex. In the last decade this problem hasbecome widespread. Evidenced by the significant increase in thenumber of drug abusers or addicts, along with the increasingdisclosure of drug crime cases, the pattern of which isincreasingly diverse and the syndicate network is getting moremassive. The Indonesian people, and even the world community,in general, are currently facing a very worrying situation due tothe widespread illegal use of various types of drugs. This concernis getting sharpened due to the rampant illicit trafficking ofnarcotics which has spread to all levels of society, includingamong the younger generation. This will greatly affect the life ofthe nation and state in the future. The behavior of some teenagerswho have clearly ignored the values, norms and laws that applyin people's lives is one of the causes of the rise of drug use amongthe younger generation. In everyday life in the midst of societythere are still many teenagers who still abuse drugs.The purpose of this service activity is to increase the knowledgeof adolescents by educating them about the dangers of juveniledelinquency which will impact their future, one of the negativeeffects of which is the dangers of narcotics among adolescents.The implementation method that we do is the Communication,Information, and Education counseling method using PowerPoint media. And the results of the counseling that we did tostudents of SMK Negeri 2 Setu, Bekasi, namely being able tounderstand well and also look interactive and be able to answerquestions that our group asked about the influence of juveniledelinquency and narcotics.